Bridging methods and disciplines: an Architectural Pedagogy for Rural Areas Communities (EAAE Annual Conference Proceedings, 2023)
Architectural pedagogy in rural areas necessitates a thoughtful consideration of both methodological and disciplinary approaches within educational process. Inner areas, which suffers from constant depopulation, lack of connection, and richness of historical/natural heritage, are entangled to a complex multiplicity of design scenarios.